2020
DOI: 10.1103/physrevd.101.125006
|View full text |Cite
|
Sign up to set email alerts
|

Double copy structure and the flat space limit of conformal correlators in even dimensions

Abstract: We analyze the flat space limit of 3-point correlators in momentum space for general conformal field theories in even spacetime dimensions, and show they exhibit a double copy structure similar to that found in odd dimensions. In even dimensions, the situation is more complicated because correlators contain branch cuts and divergences which need to be renormalized. We describe the analytic continuation of momenta required to extract the flat space limit, and show that the flat space limit is encoded in the lea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
65
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 52 publications
0
65
0
Order By: Relevance
“…At three-points, the double copy amounts to simply squaring gauge theory amplitudes into gravitational ones. The analogous statement for conformal correlators in momentum space is more intricate and was worked out in [30,31]. In particular these references demonstrated that general solutions of the conformal Ward identities involving currents and stress tensors can be related via a double copy in the flat space limit, and this relation can be extended beyond the flat space limit in three dimensions (i.e.…”
Section: Jhep02(2021)194mentioning
confidence: 92%
“…At three-points, the double copy amounts to simply squaring gauge theory amplitudes into gravitational ones. The analogous statement for conformal correlators in momentum space is more intricate and was worked out in [30,31]. In particular these references demonstrated that general solutions of the conformal Ward identities involving currents and stress tensors can be related via a double copy in the flat space limit, and this relation can be extended beyond the flat space limit in three dimensions (i.e.…”
Section: Jhep02(2021)194mentioning
confidence: 92%
“…One of the advantages of the CHY formalism in flat space is that it manifests various double-copy relations between JHEP11(2020)158 amplitudes in gauge and gravity theories [18,92], which are completely obscured from the Feynman-diagram point of view. One may hope that a similar structure might extend to AdS space (see related work [93,94] for 3-point correlators in momentum space). However, our construction reveals an interesting obstruction to the naive version of double copy in AdS.…”
Section: Jhep11(2020)158mentioning
confidence: 97%
“…the Schwinger-Keldysh formalism [33][34][35][36][37][38][39]. 5 For further work on AdS/CFT in momentum space see [60][61][62][63][64][65][66][67][68].…”
Section: Jhep11(2020)073mentioning
confidence: 99%